2019 AEIT International Conference of Electrical and Electronic Technologies for Automotive (AEIT AUTOMOTIVE) 2019
DOI: 10.23919/eeta.2019.8804519
|View full text |Cite
|
Sign up to set email alerts
|

Performance of LoRa for Bike-Sharing Systems

Abstract: Today bike sharing systems are becoming popular in many cities as short-distance transit vehicles. More than 18 million bicycles are available worldwide for public use and one of the main problems that afflicts such sharing systems is the loss of bikes, which can be stolen or simply left in unknown locations. Thus, many bikes are docked or tracked using GPS and costly cellular connections.In this paper, we consider the emerging Long Range (LoRa) technology for use in bike sharing systems. LoRa exploits free IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Bike-sharing systems are another part of cities and bikes are assets and resources of cities. The authors in [130] mentioned that one of the problems that afflicts bike-sharing systems are the loss of bikes. They study in simulation the scalability limits of a typical LoRaWAN for bike-sharing systems and showed that the performance of LoRaWAN in crowded scenarios can be quite limited when using high SFs and that fading has a moderate impact on the cell capacity.…”
Section: Localization Methods In Smart Citymentioning
confidence: 99%
“…Bike-sharing systems are another part of cities and bikes are assets and resources of cities. The authors in [130] mentioned that one of the problems that afflicts bike-sharing systems are the loss of bikes. They study in simulation the scalability limits of a typical LoRaWAN for bike-sharing systems and showed that the performance of LoRaWAN in crowded scenarios can be quite limited when using high SFs and that fading has a moderate impact on the cell capacity.…”
Section: Localization Methods In Smart Citymentioning
confidence: 99%
“…When the utilization percentage of the crane and the health status of the crane are known, then future management, maintenance, and planning will be able to be executed to prevent an unexpected event like crane shutting down or accidents that will cause a delay to the working schedule. Internet of things (IoT) had been implemented in various monitoring projects using different kinds of wireless technologies and sensors [2]- [12]. Previous research show long range (LoRa) can operate at a maximum distance of around 300 meters due to the types of antennas used in the projects, where normally a good quality of LoRa antenna can reach up to a few kilometers of distances [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional WSN implementation for tracking applications involves 2G/3G mobile network [4]. However, Low Power Wide Area Networks (LPWANs) technologies offer a lower power consumption [4,6]. In particular, LoRa allows a wide coverage area (i.e., 1-10Km [5]), with low consumption [7] using unlicensed spectrum bands (i.e., low-ers system operating costs [8]).…”
Section: Introductionmentioning
confidence: 99%